PENGARUH INTERNAL PERUSAHAAN, EKSTERNAL AUDIT, DAN KOMITE AUDIT TERHADAP AUDIT DELAY DI PERUSAHAAN GO PUBLIC DI INDONESIA - Tias, Fauziah Wahyuning; Triani, Ni Nyoman Alit (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2014)
Audit delay is the time difference between the date of the financial statements and independent auditor’s report. This study aims to identify and analyze whether the debt-to-equity ratio (DER), gain or loss suffered by the company, the size of the firm, the auditor’s opinion, the size of the audit committee and the number of audit committee meetings to audit delay in the manufacturing companies listed on the Indonesian Stock Exchange. The sampling technique used in this study was purposive sampling and obtained a sample of 31 companies. This research was conducted in the period 2008 to 2012. The data used are the financial statements, annual reports and ICMD. Multiple regression method is used to prove the hypothesis. Testing in this study using SPSS version 21. The results of this study indicate that the debt-to-equity ratio (DER), gain or loss suffered by the company, the size of the firm, the auditor’s opinion, the size of the audit committee and the number of audit committee meetings simultaneously affect the audit delay . Partially, the audit opinion affect the audit delay. Other variables such as the debt-to-equity ratio (DER), gain or loss suffered by the company, the size of the firm, the size of the audit committee and the number of audit committee meetings does not affect the audit delay.